Organic mass and protein extraction from secondary sewage sludge via multi-step physical alkali- and acid-based treatment - Skripsts, Eriks; Klaucans, Elvis; Mezule, Linda (Frontiers in Chemical Engineering, 2024)
Lately the perception of sewage sludge has shifted from a waste to a resource, leading to various technology proposals for its management and resource recovery. This study explores a two-step sewage sludge treatment using different pathways: physical-alkali followed by physical-acid, and physical-acid followed by physical-alkali hydrolysis to understand the efficiency of organic matter (OM) and Kjeldahl nitrogen extraction, and protein solubilization. Hydrolysis of the sewage sludge was performed with 3 M H2SO4 and 2.8 M NaOH and combined with a physical treatment - thermal, ultrasonication, microwave irradiation, and cavitation. The results showed that cavitation chemical hydrolysis in an alkaline environment (CCH-alkali) extract the highest amount of OM – up to 79.0%. If further cavitation chemical hydrolysis in acid environment (CCH-alkali-acid) is performed, OM extraction reaches up to 90.2%. Physical-alkali treatment showed better performance in resource recovery from the secondary sludge (SS) in both treatment steps. The highest protein extraction rate of 23 046 mg/L in the supernatant was obtained using SS treatment with microwave chemical hydrolysis in an alkaline environment (MCH-alkali). Despite physical-acid treatment resulted in reduced protein solubilization and OM extraction, it provides higher protein hydrolysis rate. Organic nitrogen compounds were better extracted with thermal-alkali treatment method reaching up to 95.3 % removal. The study showed that different physical treatment methods demonstrate selective resource recovery or extraction performance.